A novel Triticum durum Annexin 12 protein: Expression, purification and biological activities against Listeria monocytogenes growth in meat under refrigeration. (June 2020) - Hsouna, Anis Ben; Ben Saad, Rania; Trabelsi, Imen; Ben Romdhane, Walid; Brini, Faiçal; Ben Salah, Riadh
Abstract: The present study was undertaken to investigate the expression, purification and biological activities of a novel Triticum durum Annexin 12 protein (TdAnn12). The findings indicated that the molecular weight of the purified TdAnn12 was estimated to 35 kDa. The purified TdAnn12 protein was modulated by, Methyl-jasmonate, and ethephon treatments. The purified TdAnn12 protein displayed good antimicrobial activities against 9 tested pathogenic bacteria. The antioxidant activities showed that TdAnn12 displayed an excellent DPPH scavenging ability with an IC50 of 8.33 μg/ml and a strong Beta-carotene bleaching inhibition after 120 min of incubation with an IC50 of 2 μg/ml the cytotoxic effects of the TdAnn 12 showed that HepG2 and MCF-7 were examined by MTT assay. The IC50 values were 250.35 and 400.25 μg/ml for HepG2 and MCF-7 cells, respectively. The inhibitory effects of this TdAnn12 was assessed in vivo against Listeria monocytogenes, inoculated in minced beef meat at 6.10 5  CFU/g amended with different concentrations of the purified TdAnn12 and stored at 4 °C for 21 days. Results showed an excellent inhibitory effect of TdAnn12 of this pathogenic bacterium at 4 °C. Overall, the TdAnn12 have potential application as active ingredients in food and pharmaceutical industry. Highlights: The purified TdAnn12 was estimated to 35 kDa. TdAnn12 protein was modulated by, Methyl-jasmonate, and ethephon treatments. TdAnn12 protein displayed good antimicrobial activities. TdAnn12 displayed an excellent DPPH scavenging ability. Cytotoxic effects of the TdAnn 12 showed that HepG2 and MCF-7 were examined by MTT assay.